Faktor Psikososial dan Gaya Hidup dengan Pertambahan Berat Badan Ibu Selama Hamil di Wilayah Kerja Puskesmas Mereubo Kabupaten Aceh Barat - Nanda Norisa; Nora Usrina; Evi Zahara; Munazar Munazar; Putri Raisah (Malahayati Nursing Journal, 2024)
ABSTRACT Psychosocial changes during pregnancy cause anxiety which triggers an increase in the hormone’s progesterone, estrogen and HCG (Human Choionac Gonadotropin). Anxiety occurs due to the inability of pregnant women to adapt to changes in the pregnancy process, thereby stimulating increased anxiety and nausea and vomiting during pregnancy. Anxiety is influenced by factors including education, knowledge, work, and family support. Research questions: whether there is a link between psychosocial facts and lifestyle with the weight of the mother during pregnancy in Puskesmas Mereubo district of West Aceh. To determine the relationship between psychosocial and lifestyle factors and maternal weight during pregnancy at the Mereubo Community Health Center, West Aceh Regency. This research uses a quantitative type of research with a cross sectional approach. The subjects in this research were mothers who had given birth with a maximum age of 6 months, who were in the working area of the Mereubo Community Health Center, West Aceh Regency. This research will be carried out for 6 months starting in April - September 2023. The research location will be carried out in the working area of the Mereubo Community Health Center, West Aceh Regency. The instrument used in this research was a questionnaire, each variable containing 10 - 15 statement items. Data were analyzed using the chi-square test with a p value 0.05. There is a significant relationship between stress levels, social support, marital satisfaction, and lifestyle and maternal weight gain during pregnancy in the Mereubo Community Health Center working area, West Aceh Regency (p0.05). There is no significant relationship between anxiety levels and maternal weight gain during pregnancy in the Mereubo Community Health Center working area, West Aceh Regency (p0.05). Conclusion: There is a relationship between stress levels, social support, marital satisfaction, and lifestyle and maternal weight gain during pregnancy. There is no relationship between anxiety levels and maternal weight gain during pregnancy.  Keywords: Psychosocial Factors, Lifestyle, Pregnant Women, Weight Gain  ABSTRAK Perubahan psikososial masa hamil menimbulkan kecemasan yang memicu peningkatan hormone progresteron, estrogen dan HCG (Human Choionac Gonadotropin). Kecemasan terjadi akibat ketidakmampuan Ibu hamil dalam beradaptasi terhadap perubahan proses hamil sehingga merangsang peningkatan cemas dan mual muntah kehamilan. Cemas dipengaruhi oleh faktor diantararanya pendidikan, pengetahuan, pekerjaan dan dukungan keluarga. Apakah ada hubungan faktok psikososial dan gaya hidup dengan berat badan ibu selama hamil di Puskesmas Mereubo Kabupaten Aceh Barat. Tujuan Penelitian untuk mengetahui hubungan faktok Psikososial dan Gaya Hidup dengan Berat Badan Ibu Selama Hamil di Puskesmas Mereubo Kabupaten Aceh Barat. Penelitian ini menggunakan jenis penelitian kuantitatif dengan pendekatan cross sectional. Subjek dalam penelitian ini yaitu Ibu yang telah melahirkan dengan usia bayi maksimal 6 bulan, yang berada di wilayah kerja Puskesmas Mereubo Kabupaten Aceh Barat. Penelitian ini akan dilaksanakan selama 6 bulan dimulai pada bulan April - September 2023. Lokasi penelitian dilaksanakan di wilayah kerja Puskesmas Mereubo Kabupaten Aceh Barat. Instrumen yang digunakan pada penelitian ini adalah satu buah kuisioner, masing-masing variabel berisi 10 – 15 item pernyataan. Data dianalisis menggunakan uji chi-square dengan nilai p0.05. Ada hubungan secara signifikan antara tingkat stress, dukungan social, kepuasan perkawinan, dan gaya hidup dengan pertambahan berat badan ibu selama hamil di wilayah kerja Puskesmas Mereubo Kabupaten Aceh Barat (p0.05). Tidak ada hubungan secara signifikan antara tingkat kecemasan dengan pertambahan berat badan ibu selama hamil di wilayah kerja Puskesmas Mereubo Kabupaten Aceh Barat (p0.05). Ada hubungan antara tingkat stress, dukungan social, kepuasan perkawinan, dan gaya hidup dengan pertambahan berat badan ibu selama hamil. Tidak ada hubungan antara tingkat kecemasan dengan pertambahan berat badan ibu selama hamil. Kata Kunci: Faktor Psikososial, Gaya Hidup, Ibu Hamil, Pertambahan Berat Badan